Alopecia Areata: A Case Report - Peter Nugraha Soekmadji; Tamara Damayanti; Aurellia Tirza Amelinda; Della Hestia Suyanto; Khusnul Hotimah Amimatori; Nindia Aru Khairana (Medical Clinical Update, 2023)
The frequent asymptomatic condition alopecia areata (AA) is characterized by the sudden start oftotal hair loss in a sharply defined, typically spherical area. Complicated autoimmune diseasesboth hereditary and environmental factors affected the susceptibility to and severity of the dis-ease. About 34-50% of patients experience a spontaneous recovery within a year, while patientsmay go through many alopecia bouts. The purpose of this case report is to go over the identifica-tion and management of alopecia areata.